2022
DOI: 10.1101/2022.08.04.502824
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Parallel evolution of reduced cancer risk and tumor suppressor duplications in Xenarthra

Abstract: The risk of developing cancer is correlated with body size and lifespan within species, but there is no correlation between cancer and either body size or lifespan between species indicating that large, long-lived species have evolved enhanced cancer protection mechanisms. Previously we showed that several large bodied Afrotherian lineages evolved reduced intrinsic cancer risk, particularly elephants and their extinct relatives (Proboscideans), coincident with pervasive duplication of tumor suppressor genes (V… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Other studies, which had very large samples but that combined data from multiple species, reported cancer in only 14/1800 (0.78%, 95% CI: 0.04-0.13%) and 2/2000 (0.01%, 95% CI: 0.00–0.04%%) necropsies ( Figure 1A ; Figure 1 – source data 1 ). Next, we compared neoplasia prevalence in Cetacea to other Therian mammals from three published studies that included pathology reports from 37 (Boddy et al, 2020) and 191 (Vincze et al, 2022) species of Therian mammals, and a large dataset of Xenarthrans compiled from multiple published sources (Vazquez et al, 2022); The dataset includes cancer prevalence data from 244 species. As a group the mean prevalence of neoplasia in Cetacea was 1.4% (95% CI: 1.07– 1.70%) when aggregated across all datasets and excluding St. Lawrence estuary belugas ( Figure 1B ; Figure 1 – source data 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies, which had very large samples but that combined data from multiple species, reported cancer in only 14/1800 (0.78%, 95% CI: 0.04-0.13%) and 2/2000 (0.01%, 95% CI: 0.00–0.04%%) necropsies ( Figure 1A ; Figure 1 – source data 1 ). Next, we compared neoplasia prevalence in Cetacea to other Therian mammals from three published studies that included pathology reports from 37 (Boddy et al, 2020) and 191 (Vincze et al, 2022) species of Therian mammals, and a large dataset of Xenarthrans compiled from multiple published sources (Vazquez et al, 2022); The dataset includes cancer prevalence data from 244 species. As a group the mean prevalence of neoplasia in Cetacea was 1.4% (95% CI: 1.07– 1.70%) when aggregated across all datasets and excluding St. Lawrence estuary belugas ( Figure 1B ; Figure 1 – source data 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Population doubling time is proportional to the cumulative length of individual cell cycle phases, particularly the length of G 1 (Blank et al, 2018). Therefore, we performed a thorough literature review and assembled a dataset of population doubling times from 60 species of Eutherian mammals (Vazquez et al, 2022). While there was considerable variation in population doubling times between species, whale cells had similar doubling times as other species of mammals ( Figure 7A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations